Mitigasi dampak kebisingan bandara terhadap kehidupan pemukiman sekitar bandara SSK II Pekanbaru - Eko Hendi Saputra; Yusni Ikhwan Siregar; Hafidawati Hafidawati (Jurnal Zona, 2020)
This study aims to determine the level of noise caused by flight activities at Sultan Syarif Kasim II Airport Pekanbaru, analyze noise levels that occur due to flight activities at Sultan Syarif Kasim II Airport Pekanbaru and analyze efforts to control the negative impact of airport noise on the living environment of community settlements. around Sultan Syarif Kasim II Airport Pekanbaru. This research uses field observation method, which is making direct observations at the research location by looking at the condition of the location and the suitability of the location which is the sampling point of the study (the noise level boundary at Sultan Syarif Kasim II Airport). Observations were made for 16 hours (Ls) at an interval of 06.00 - 22.00. Measurement of sound pressure level is carried out on holidays (Sunday) and weekdays (Monday), which starts on November 1, November 2, November 8, and November 9, 2020, which is carried out in residential areas around Sultan Syarif Kasim II Airport Pekanbaru, which are spread across 6 measurement points where the measurement of sound pressure level is done in duplicate, namely: Jl. Kaswari (point 1), Jl. Rawa Indah II (Point 2), Jl. Rawa Indah III (Point 3), Jl. Cinnamon (Point 4), Jl. Pahlawan Kerja gg.Pala 49 (Point 5) and Jl. Nur Asiyah (Point 6) The results of the processing of noise measurement data were made of a mapping model using surfer 11 software and to clarify the noise description at the sampling location, the map of the results of surfer 11 software processing was plotted on the airport area map.     Based on the results of measurements of noise levels around Sultan Syarif Kasim II airport, it is known that the location of point 1 (Jl. Rawa Indah II) experienced the highest noise exposure. These results indicate the location of point 1 should receive serious attention for the people who live around the airport, because the impact of airport noise has the potential to negatively affect the lives of residential communities. From the observations, it was also known that the level of noise attenuation was still low, both in terms of trees around the settlement and height, walls and fences were still not effective at reducing noise.         Based on the results of measurements of noise levels around Sultan Syarif Kasim II airport, it is known that the location of point 1 (Jl. Rawa Indah II) experienced the highest noise exposure. These results indicate that the location of point 1 should receive serious attention for the people who live around the airport, because the impact of airport noise has the potential to negatively affect the lives of residential communities. From the observations, it was also known that the level of noise attenuation was still low, both in terms of trees around the settlement and height, walls and fences were still not effective at reducing noise.         From the results of the research that has been done, several mitigation strategies can be formulated to reduce noise levels around Sultan Syarif Kasim II airport. Planting plants in accordance with the needs of controlling or reducing noise in human settlements. Tree categories suitable for planting in residential areas around the airport are: shady trees that can be planted tightly or with lots of leaves that can grow to a height of about 4 - 15 m (such as acacia, mahogany, flamboyant, ironwood or banyan trees, bamboo or cypress)